1000 Fandangos. Amanhecer - Bertolo, Gabriel (2020)
This thesis search, through an intensive ethnographic description, to inquire about the caiçaras movements around their most celebrated aesthetical-political expression, the fandango caiçara – acknowledged as a Brazilian Intangible Heritage by the Institute of National Historical and Artistic Heritage (IPHAN). Through its development/performance, the investigation shifts its points of departure and becomes an ethnography of culture as comprehended by fandangueiros. Rather than “explain” the fandango by caiçara culture, the thesis becomes a set of episodes that aim to speculate about culture through their fandangos. In this sense, it becomes of greater importance the thesis elaborated by fandangueiros caiçaras of the Brazilian south and south-eastern coast, especially of Cananéia-SP, about what is culture, how it unfolds, transform and maintain in space/time. Thus, through its artisan craft and its poetic, choreographic, musical, and musicological expressions, it is sought to understand the place and the time that the fandangos inhabit and make inhabit: the Caiçara Territory.